Neurotic tendency of smokers - Soewadi, Soewadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
The harniful health effects of tobacco smoking have been reported by many experts. Death rates are unifomily higher among smokers than among non-smokers, in both sexes and whatever the age at death. Cigarette smoking is also considered to be responsible for the great majority of cases of lung cancer. There is evidence that the influence of smoking in ischaemic heart disease is not only independent, but also synergistic with other risk factors such as hypertension and high blood cholesterol. Surveys in many countries show that smokers cough more than non-smokers and produce more sputum. Cigarette smoking acts independently and synergistically with other risk factors contributing to bronchitis.Many experts agree that the smoking problem is now a worldwide epidemic and causing serious diseases. Therefore, studying the problem associated with tobacco should include, specifically the harmful health effects of smoking.The study was carried out in Yogyakarta among senior high schools student. The aim of the study is to test the hypothesis that there is a relationship between neurotic tendency with smoking. Randomized sampling method were done for the analytic-descriptive design of the study.Results showed that there is a significant difference between group of smokers and non-smokers according to the tendency of neurosis (p<0.05). Results also showed that there is a correlation between the tendency of neurosis and smoking (Contingency-Coeff.=0.44)Key Words: smoking - smoker prevalence - smoker relatives - neurosis - psychiatric intervention